2016
DOI: 10.1177/1468794116679726
|View full text |Cite
|
Sign up to set email alerts
|

Criteria for quality in qualitative research and use of freedom of information requests in the social sciences

Abstract: Access to information (ATI) and freedom of information (FOI) requests are an under-used means of producing data in the social sciences, especially across Canada and the United States. We use literature on criteria for quality in qualitative inquiry to enhance ongoing debates and developments in ATI/FOI research, and to extend literature on quality in qualitative inquiry. We do this by building on Tracy’s (2010) article on criteria for quality in qualitative inquiry, which advances meaningful terms of reference… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(32 citation statements)
references
References 60 publications
(101 reference statements)
0
30
0
2
Order By: Relevance
“…6. Transferability is another expected feature of discussion in qualitative submissions (Walby & Luscombe, 2016 ). Statistical generalizability is not desirable or reasonable in qualitative research, but qualities of 'thick description' that present findings with categories identified that are appropriately defined and supported by sufficient data are expected.…”
Section: Evaluation Criteria For Qualitative Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…6. Transferability is another expected feature of discussion in qualitative submissions (Walby & Luscombe, 2016 ). Statistical generalizability is not desirable or reasonable in qualitative research, but qualities of 'thick description' that present findings with categories identified that are appropriately defined and supported by sufficient data are expected.…”
Section: Evaluation Criteria For Qualitative Researchmentioning
confidence: 99%
“…Rigor is important but, from the perspective of some transformative paradigms, this understanding of rigor is problematically limited, as it excludes consideration of the motivation and purpose of research and the social or community‐related effects of research outcomes (Dellinger & Leech, ). All researchers, whether qualitative or quantitative, might agree that rigorous research is not necessarily ‘good’ research; many who undertake qualitative research prioritize additional criteria relating to professional and ethical practice as the basis from which to establish the value of the research endeavor (Barusch et al, ; Walby & Luscombe, ).…”
Section: The Nature Of Qualitative Research and The Nature Of Rigormentioning
confidence: 99%
“…In more methodologically oriented discussions, scholars (e.g., Walby and Luscombe 2017;Jiwani and Krawchenko 2014;Savage and Hyde 2014;Walby and Larsen 2012) have elaborated how FOI requests can enhance social inquiry. Yet there is no guarantee that FOI researchers will receive full disclosure, making consistent use of FOI requests challenging for social science researchers (Monaghan 2015).…”
Section: Foi Brokering and Law In The Wild In Comparative Perspectivementioning
confidence: 99%
“…The thick description offered in our study, and the deep contextualised understandings reported in our findings, offers a basis for consideration of application to other contexts (Walby and Luscombe 2017;Levitt, Creswell, Josselson, Bamberg, Frost and Suárez-Orozco 2018). It would be worthwhile to return to our research sites to pursue follow-on inquiry, looking at how the conversation has developed not least in the run up to the subsequent REF.…”
Section: Limitations and Further Researchmentioning
confidence: 79%